2008
DOI: 10.1111/j.1540-8159.2008.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Atrioventricular Tachycardia Degenerating to Atrial Flutter/Fibrillation in the Young with Wolff‐Parkinson‐White

Abstract: AF with RVR occurred following AVRT induction during EPS in 34% of our WPW patients, typically associated with right-sided AP locations. Time intervals for RVR to degenerate into ventricular fibrillation and lead to SCD are yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
(84 reference statements)
0
8
0
1
Order By: Relevance
“…It has also been suggested with less unanimity that other clinical associations may be important and useful markers: the nature and severity of clinical presentation,13 the presence of multiple pathways and an anatomical location of the AP in the right anteroseptal AV groove,11 20 and the inducibility of any SVT (including both AV reciprocating tachycardia and atrial fibrillation) on electrophysiological study 7. Identifying a reduced and reliable set of risk factors from these different studies is complicated by the fact that some are likely to be electrophysiologically associated.…”
Section: Risk Stratification In Wpwmentioning
confidence: 99%
“…It has also been suggested with less unanimity that other clinical associations may be important and useful markers: the nature and severity of clinical presentation,13 the presence of multiple pathways and an anatomical location of the AP in the right anteroseptal AV groove,11 20 and the inducibility of any SVT (including both AV reciprocating tachycardia and atrial fibrillation) on electrophysiological study 7. Identifying a reduced and reliable set of risk factors from these different studies is complicated by the fact that some are likely to be electrophysiologically associated.…”
Section: Risk Stratification In Wpwmentioning
confidence: 99%
“…Inducibility of AVRT, a shorter APERP (Ͻ240 ms), a shorter pre-excited RR interval during induced AF (Ͻ240 ms), the presence of multiple pathways, and septal and right-sided pathway locations appear to identify a higher-risk group (3,(5)(6)(7).…”
Section: See Page 275mentioning
confidence: 94%
“…In one reported series, spontaneous atrial fibrillation was seen in 4% of children with WPW syndrome, with 22% of children demonstrating atrial fibrillation during electrophysiologic study (Lee et al, 2004). Degeneration of supraventricular tachycardia into atrial fibrillation was seen in 51% of 53 young patients with WPW syndrome, with 34% having a rapid ventricular response rate (Harahsheh et al, 2008). In another study of 62 asymptomatic children with pre-excitation on their electrocardiogram, supraventricular tachycardia was initiated in 58% and atrial fibrillation was observed in 13% (Sarubbi et al, 2005).…”
Section: Atrial Fibrillation In Children Without Structural Heart Dismentioning
confidence: 98%